Spiritual-Enlightenmental Work In Uzbekistan's Higher Educational Institutions (Historical Analysis) - Ural, Makhmudov (Academicia Globe: Inderscience Research, 2025)
The article is devoted to the analysis of the processes of implementing spiritual and educational work in higher educational institutions of Uzbekistan, considering the importance and effectiveness of these processes using the example of the Kokand State Pedagogical Institute. The article discusses the types of spiritual and educational activities carried out at the institute, their role in student education and their impact on the teaching process. Also, proposals are put forward for further improvement of spiritual and educational work.